Pemberian ASI Eksklusif dengan Kejadian Stunting pada Balita - Rilyani Rilyani; Riska Wandini; Widia Dwi Lestari (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; Short and very short, known as stunting, are nutritional status based on the height index for age. The purpose of knowing the relationship between exclusive breastfeeding and the incidence of stunting. Methodology; This study was conducted using analytic observations with a cross-sectional approach, the population in this study were all children under five in the working area of Puskesmas X, the number of samples used was 82. Results; showed that 18 children who were not stunting were given exclusive breastfeeding (52, 9%) Stunting of children under five who were given exclusive breastfeeding were 16 children (47.1%). As many as 12 children under five who were not stunting (25.0%) were not exclusively breastfed and as many as 36 children under stunting (75.0%) were not exclusively breastfed. Conclusion; There is a significant relationship between exclusive breastfeeding and the incidence of stunting in the working area of Puskesmas X Lampung Tengah